A new species of Characella Sollas, 1886 (Tetractinellida; Demospongiae; Porifera) from deeper waters off the coast of Brazil - Dias, Alan; Santos, George Garcia; Pinheiro, Ulisses (Zootaxa, 2019)
Sponges of the Family Pachastrellidae Carter, 1875 are distributed worldwide and found generally in deep water. Up to date, only four species are known for the Brazilian coast (Muricy 2018): Characella aspera Sollas, 1886, C. capitolii Mothes et al. 2007, C. pachastrelloides (Carter, 1876), and Pachastrella monilifera Schmidt, 1868. In this study, a new species of Characella is described from the mesophotic zone off Bacia Potiguar (Rio Grande do Norte State, Northeastern Brazil). The specimen was preserved in 80% ethanol and deposited in the Porifera Collection of the Universidade Federal de Pernambuco (UFPEPOR). Taxonomic comparisons were made with data tabulated for all species of Characella available in the World Porifera Database (van Soest et al. 2018).